口底部に発生した炎症性筋線維芽細胞腫の1例 - 菅原, 圭亮; 伊藤, 和宏; 橋本, 和彦; 片倉, 朗; 別所, 央城; 松坂, 賢一 (日本口腔外科学会雑誌, 2021)
Inflammatory myofibroblastic tumors (IMT) are spindle cell proliferations with a characteristic fibro-inflammatory appearance, originally referred to as an inflammatory pseudotumors or plasma cell granulomas. We report a case of IMT in the floor of the mouth of a 41-year old female. The patient had a tumor in the floor of her mouth, measuring 35 × 30 × 20 mm. Magnetic resonance imaging (MRI) showed a lesion with high signal intensity on T1-weighted images. We performed resection under local anesthesia. Histological examination of the surgically removed lesion showed that the proliferative spindle cell was found inside the lipoma. There was no evidence of recurrence after five years. IMT are usually benign, however there are also reports of recurrence and malignant transformation. Careful long-term follow-up using MRI etc. is thought to be necessary.